Synthesis of shape memory electroconductive polyurethane with self-healing capability as an intelligent biomedical scaffold for bone tissue engineering. (3rd May 2021) - Shaabani, Alireza; Sedghi, Roya
Abstract: Electrically conductive polymeric materials are known as a special class of intelligent bioactive materials capable of regulating cellular behaviors of human adipose-derived mesenchymal stem cells, especially their differentiation to bone tissue. Here the synthesis of electroactive self-healing polyurethane scaffolds (PUAT) with shape memory ability based on aniline trimer and disulfide bonds are reported. The prepared scaffolds were characterized by FTIR, tensile test, water contact angle, electrical conductivity, and degradation test. The PUAT5 scaffold (containing 5% aniline trimer) exhibited excellent self-healing (>95%) and shape memory properties with shape recovery ratio (>95%, ~30 s at 40 °C) and shape fixity ratio (>96%) at a temperature close to the physiological temperature. The PUAT5 significantly promote the human adipose-derived mesenchymal stem cell adhesion and proliferation compared to PUAT0 and TCP. Also, the gene expression level of RUNX2, COL1, ALP, and OCN of PUAT5 were significantly enhanced after 21 days, in line with the increased maturity of extracellular matrix and mineralization. Furthermore, almost 75% of the bone volume has been recovered at 8 weeks post-surgery while the control group showed 26% recovery. The In vitro and In Vivo results suggested that these multifunctional engineered constructs have great potential in repairing various bone defects. Graphical abstract: Image 1 Highlights: The composite scaffold shows outstanding shape memory properties. The AT-contained scaffolds indicated excellent self-healing capability at low temperature. PUAT scaffolds could well support hASC cells to attach, grow and proliferate. The introduction of aniline trimer significantly improved osteogenesis In vitro and In vivo.